Psychomotricity and mathematical notions in 5 year old students. Educational institution N° 599 “Rose de América” - Puente Piedra - Lima - Marcelo Matias, María Elena (2023)
The general objective of this research study is to determine if there is a relationship between psychomotor skills and mathematical notions in 5-year-old students of Educational Institution 599. Four specific objectives were also proposed to determine the relationship that exists between the dimensions of psychomotor skills; gross motor, fine motor and visual-motor skills with the dimensions of mathematical notions that are classification, correspondence, serialization and conservation of quantity. The type of research we used was basic descriptive at a relational level with a nonexperimental descriptive design, it is a quantitative research of a cross-sectional prospective study because the instruments are applied after the study has started only once; The population was made up of 40 5-year-old students from the educational institution 599 Rosa de América. To collect data, the observation technique was used; as evaluation instruments, an observation sheet was made for the independent variable and a test of mathematical notions for the dependent variable that met the qualities of validity and reliability by experts in the field.